Scalable Collaborative Infrastructure for a Learning Healthcare System (SCILHS): Architecture. (12th May 2014) - Mandl, Kenneth D; Kohane, Isaac S; McFadden, Douglas; Weber, Griffin M; Natter, Marc; Mandel, Joshua; Schneeweiss, Sebastian; Weiler, Sarah; Klann, Jeffrey G; Bickel, Jonathan; Adams, William G; Ge, Yaorong; et al.
Abstract: We describe the architecture of the Patient Centered Outcomes Research Institute (PCORI) funded Scalable Collaborative Infrastructure for a Learning Healthcare System (SCILHS, http://www.SCILHS.org ) clinical data research network, which leverages the 48 billion dollar federal investment in health information technology (IT) to enable a queryable semantic data model across 10 health systems covering more than 8 million patients, plugging universally into the point of care, generating evidence and discovery, and thereby enabling clinician and patient participation in research during the patient encounter. Central to the success of SCILHS is development of innovative 'apps' to improve PCOR research methods and capacitate point of care functions such as consent, enrollment, randomization, and outreach for patient-reported outcomes. SCILHS adapts and extends an existing national research network formed on an advanced IT infrastructure built with open source, free, modular components.